The road home - Yu Zha; Timou Zhang; Ziyi Zhang; Honglei Sun; Hao Zheng; Yulian Zhao; Yong Hou; Cao Juiping; Zhai Ru; San Bao; Bao Shi (Sony Pictures Classics : Distributed by Columbia TriStar Home Entertainment, [2001], 2000)
As a son helps his mother arrange for the burial of his father in the traditional Chinese custom of his mother's village, the beautiful and touching story of his parent's courtship unfolds. His father was from the city and came to his mother's village to become the schoolmaster. In the days of arranged marriages, the son discovers that his parents marriage was the first marriage based on love.